Informed consent: knowledge, attitude and practice of the researchers in a postgraduate institute of Bangladesh (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):215-20.The abstract of this article is available on the PubMed website